The Influence of Price Fairness to Customer Satisfaction - Denny Yoristar (Business and Entrepreneurial Review, 2007)
The objective of this research is to analyze the influence of price fairness, customer satisfaction, empirically demonstrate the influence of perceived price fairness that can be broken down into price perception, consumer vulnerability, price offer fairness and price procedure fairness. Methodology used in this research is descriptive analysis, which is to identify characteristics of variables under certain circumstances and to scribal down the response of automobile customers in Jakarta, Bekasi, Depok, and Tangerang. Variables measurement ranked from price perception, consumer vulnerability, price offer fairness, price procedure fairness, satisfied with dealer's service, satisfied with delivery car and satisfied with purchase that the result would be used as information to manage automobile sales. The collected data was analyzed using multiple regression analysis. This research concluded that variable of price perception and perceived vulnerability has a significant impact toward price offer fairness, variable of price offer fairness and price procedure fairness has no effect toward satisfied with purchase, and variable of satisfied with dealer's service and satisfied with delivery car significantly affect the satisfied with purchase variable.